Application Of Picture And Picture Learning Model To Improve Students’ Reading Through English Lessons - Anggraeni, Dian Nurvita (Prosiding University Research Colloquium, 2021)
This writing aims to improve the ability of students' interest in reading in elementary schools through the learning model. Reading is one of the important things in all kinds of learning process. Efforts to increase the reading interest of elementary school students are a shared responsibility, between the students themselves, teachers and parents. The low interest in reading students in elementary schools is one of the obstacles, the lack of desire and willingness of the students themselves, the teacher also does not require students to read books when learning is taught to students. The results showed that with Picture and Picture learning activities became more interesting and students thought to further increase their interest in reading. From the results of the analysis, it can increase the reading interest of elementary school students